UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN KEHADIRAN GURU DI SEKOLAH DASAR - Victorinie, Irnie; Maulana, Muhamad Pandu; Sandra, Yopfie (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
The purpose of this research is to identify and analyse the efforts made by the head of the school to improve the discipline of teachers' presence in primary schools. Research results show that the increased discipline of teacher attendance is influenced by a combination of strict rules, motivation, and coherence of the head of school. In addition, effective communication between teachers and the head of school and the involvement of teachers in the decision-making process also contribute to improved discipline. The results of this study show the importance of the role of the head of school in creating a good school environment and encouraging the professionalism of teachers.